Understanding the Mathematical Principles Behind Encryption and Decryption Algorithms, and Their Applications in Modern Communication and Security (Eurasian Journal of Engineering and Technology, 2023)
In our world, cybercrime abounds, Specialists uses many methods to defend security of network, as there are several ways of trying to hack it. The importance of mathematics lies in the domain of cybersecurity. One can see the strength of the current mathematical apparatus in information and Internet protection. Solving problems of security technologies such as averting cyber-attacks, secure cryptography, and risks are analyzed using different sections of math.